Functional Analysis of OsKANADI1, A Florigen Hd3a Interacting Protein in Rice (Oryza sativa L.) - Purwestri, Yekti Asih; Ogaki, Yuka; Tsuji, Hiroyuki; Shimamoto, Ko (Indonesian Journal of Biotechnology, 2012)
OsKANADI1 is considered as a florigen Hd3a interacting protein. To study the function of OsKANADI1, the expression pattern of OsKANADI1 was performed by semiquantitative RT-PCR with various wild-type tissues in the floral transition stage. The results demonstrated that OsKANADI1 was expressed in all organs of wild-type plants, but was highest in roots and leaves. We hypothesize that OsKANADI1 is a transcription factor in rice because it contains a GARP domain and posses a nuclear localization signal. To determine whether OsKANADI1 encodes a nuclear protein, full-length OsKANADI1 fused to GFP was introduced into onion epidermis cells by particle bombardment. The result revealed that OsKANADI1 was localized in the nucleus, suggesting that OsKANADI1 may be a transcription factor. Functional analysis was carried out using a reverse genetics approach to generate gain of function mutant (overexpression) and knockdown mutant (RNAi). The results showed that suppression of OsKANADI1 by RNAi displayed branching and increasing tiller number in several lines. This phenotype resembles to the Hd3a overexpressed plants indicating they possibly function in similar pathway.Key words : OsKANADI1, Transcription factor, Hd3a interacting protein, Rice